Bubble growth dynamics in nucleate pool boiling with liquid subcooling effects - Mat Nawi, Muhad Rozi (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2014)
Heat transfer in nucleate pool boiling has been characterized by very high dissipated heat fluxes whilst requiring low driving temperature differences. The rate of bubble growth and the subsequent bubble motion has a tremendous influence on the heat transfer. In order to gain a deeper understanding of the mechanisms responsible for this, basic knowledge of bubble growth dynamics is required. To this end, single isolated bubble growth dynamics from an artificial nucleation site in pool boiling has been investigated experimentally in this study.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin